Acute toxicity of pyraclostrobin and trifloxystrobin to Hyalella azteca. (23rd May 2013) - Morrison, Shane A.; Mcmurry, Scott T.; Smith, Loren M.; Belden, Jason B.
Abstract Fungicide application rates on row crop agriculture have increased across the United States, and subsequently, contamination of adjacent wetlands can occur through spray drift or field runoff. To investigate fungicide toxicity, Hyalella azteca amphipods were exposed to 2 fungicide formulations, Headline and Stratego, and their active strobilurin ingredients, pyraclostrobin and trifloxystrobin. Water‐only exposures resulted in similar median lethal concentration (LC50; 20–25 µg/L) values for formulations and strobilurin ingredients, suggesting that toxicity is due to strobilurin ingredients. These values were below concentrations that could occur following spray drift over embedded cropland wetlands. When fungicides were added to overlying water of sediment‐water microcosms, toxicity was reduced by 500% for Headline and 160% for Stratego, compared with water‐only exposures, based on the total amount of fungicide added to the systems. In addition, when fungicides were added to sediment prior to the addition of water, the reduction in toxicity was even greater, with no toxicity occurring at environmentally relevant levels. Differences in toxicity among exposure groups were explained by dissipation from water as toxicity values based on measured water concentrations were within 20% between all systems. The present study reinforces previous studies that Headline and Stratego are toxic to nontarget aquatic organisms. However, the presence of sediment is likely to ameliorate some toxicity of fungicide formulations, especially if spraying occurs prior to wetland inundation. Environ Toxicol Chem 2013;32:1516–1525. © 2013 SETAC